2017
DOI: 10.1039/c7tb01477e
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive unimolecular micelles based on amphiphilic star-like copolymers with high drug loading for effective drug delivery and cellular imaging

Abstract: A theranostic nanoplatform based on pH-responsive amphiphilic star-like copolymers for theranostic and NIR imaging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Poly [2-(diisopropylamino) ethyl methacrylate] (PDPA) and its derivates with a wide pKa range between 4.0 and 7.4 is also an important pH-responsive protonated polymer [65] . Examples include amphiphilic PEG-b-PDPA copolymer [66] and poly [2-(diisopropylamino) ethyl methacrylate]-b-poly [(ethylene glycol) methyl ether methacrylate] (PDPA-b-POEGMA) [67] . These two copolymers had a pH transition at 6.2 and exhibited much sharper and quicker pH response in the acidic endocytic organelles than many previous pH-sensitive nanosystems [68 , 69] .…”
Section: Stimuli Triggered Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Poly [2-(diisopropylamino) ethyl methacrylate] (PDPA) and its derivates with a wide pKa range between 4.0 and 7.4 is also an important pH-responsive protonated polymer [65] . Examples include amphiphilic PEG-b-PDPA copolymer [66] and poly [2-(diisopropylamino) ethyl methacrylate]-b-poly [(ethylene glycol) methyl ether methacrylate] (PDPA-b-POEGMA) [67] . These two copolymers had a pH transition at 6.2 and exhibited much sharper and quicker pH response in the acidic endocytic organelles than many previous pH-sensitive nanosystems [68 , 69] .…”
Section: Stimuli Triggered Drug Deliverymentioning
confidence: 99%
“…These two copolymers had a pH transition at 6.2 and exhibited much sharper and quicker pH response in the acidic endocytic organelles than many previous pH-sensitive nanosystems [68 , 69] . Gao et al reported star-like NPs where PDPA-b-POEGMA anchored on a β-CD core for simultaneous controllable drug delivery [67] . Due to the presence of the PDPA blocks, the copolymers were hydrophobic at pH 7.4 which enabled the efficient loading of hydrophobic drugs such as doxorubicin (DOX) in their hydrophobic layer, while an acidic environment ( e.g.…”
Section: Stimuli Triggered Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these significant differences in microenvironment, a series of stimulus-responsive polymeric micelles have been exploited to control the release of the anticancer drugs at the expected target sites. For example, researchers used the weak acidity of tumor tissues and developed a series of pH-responsive drug controlled-release systems, which can accept appropriate pH changes in response to acidic fluctuation of the tumor tissues [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The number of initiating groups on this macromolecule codes the number of arms in the synthesized star polymer. Moreover, by extension of ω-chain ends on the periphery of the star we can easily introduce a next segment to the polymer [ 22 23 ].…”
Section: Introductionmentioning
confidence: 99%